1989
DOI: 10.1016/s0006-3495(89)82792-4
|View full text |Cite
|
Sign up to set email alerts
|

Internal and external K+ help gate the inward rectifier

Abstract: Recent investigations have demonstrated substantial reductions in internal [K+] in cardiac Purkinje fibers during myocardial ischemia (Dresdner, K.P., R.P. Kline, and A.L. Wit. 1987, Circ. Res. 60: 122-132). We investigated the possible role these changes in internal K+ might play in abnormal electrical activity by studying the effects of both internal and external [K+] on the gating of the inward rectifier iK1 in isolated Purkinje myocytes with the whole-cell patch-clamp technique. Increasing external [K+] ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
2

Year Published

1990
1990
2004
2004

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 19 publications
3
41
2
Order By: Relevance
“…In the presence of Spm, the time course of the deactivation was so fast that the time constant could not be determined by the envelope test (n = 6). These findings support further the idea that Spm is the blocking molecule of the channel causing the non-conductive state C. (Ishihara et al 1989;Cohen, DiFrancesco, Mulrine & Pennefather, 1989) and in the IRK1 channel (Stanfield et al 1994a). Using the pipettes containing 1 mm free Mg2+, we confirmed that the increase of the channels in the state C also becomes slower as the depolarization becomes larger (Fig.…”
Section: Solutionssupporting
confidence: 88%
“…In the presence of Spm, the time course of the deactivation was so fast that the time constant could not be determined by the envelope test (n = 6). These findings support further the idea that Spm is the blocking molecule of the channel causing the non-conductive state C. (Ishihara et al 1989;Cohen, DiFrancesco, Mulrine & Pennefather, 1989) and in the IRK1 channel (Stanfield et al 1994a). Using the pipettes containing 1 mm free Mg2+, we confirmed that the increase of the channels in the state C also becomes slower as the depolarization becomes larger (Fig.…”
Section: Solutionssupporting
confidence: 88%
“…Time-dependent activation of Kir2.1 is dependent on external K ϩ concentration and is reduced as the external K ϩ is increased (27,28). With Kir2.1, this was shown to be due to competition between K ϩ and polyamines (28).…”
Section: Effect Of H5 Mutations On Slowmentioning
confidence: 99%
“…For the/~r channel in frog skeletal muscle fibers, "tact is <5 ms at 13~ (Leech and Stanfield, 1981). For the cardiac background/~r channel (iKl), "r~t is <5 ms at 30-370C (Kurachi, 1985;Tourneur, Mitra, Morad, and Rougier, 1987;Harvey and Ten Eick, 1988) and can be slowed down to <10 ms at 14-15~ (Saigusa and Matsuda, 1988;Ishihara et al, 1989) and <20 ms at 8-10~ (Cohen, DiFrancesco, Mulrine, and Pennefather, 1989). For the/~r channel current in bovine pulmonary endothelial cells, %ct is <5 ms at 20-23~ (Silver and DeCoursey, 1990).…”
Section: Comparison Of Intrinsic Girki Gating With Other Ir Channelsmentioning
confidence: 99%